8.M. Workshop: Researching the health effect of gender-based violence on women: challenges and implications. (30th September 2020) - ,; ,
Abstract: Violence against women is a pervasive human rights violation, which is still under-recognized despite some recent progress. From sexist ubiquitous online harassment, to physical and sexual violence that affects at least 1 in 3 women in her lifetime, this prevalent and large spectrum of violence constitutes a profound health problem. It affects women's physical and mental health, making its prevention one of the most far-reaching public health objectives. Public health research on this topic is lacking, and few large epidemiological surveys and cohorts collect data on this subject. However, research is much needed to bring to light the extent of the problem, and guide the development and implementation of effective interventions, policies, and prevention strategies. In this symposium we propose to shed light on some health effects of gender-based violence and discuss methodological issues associated with conducting research on violence against women. Through the presentation of four studies, we highlight challenges in the framing of research questions, and in defining exposure variables and collecting data in standard epidemiological studies. We also reflect on barriers and enablers we encountered and brainstorm action levers for pragmatic and ethical intervention studies. Between them, the four studies cover various types of violence and health outcomes, and touch on the involvement of several health and healthcare stakeholders. First, Barbier et al describe the prevalence of physical, sexual and psychological intimate partner violence against European women, as well as perpetrator's characteristics, using data from the European Union Agency for Fundamental Rights survey on violence against women. Second, Miani et al. reflect on the potential and limitations of using standard hospital records to measure violation of a woman's integrity during childbirth (e.g. obstetric violence) in Germany. Opportunities for intersectional analyses are also assessed. Third, El-Khoury et al. present results from the French Health barometer, a general population telephone survey, which recruited more than 25, 000 adults aged18 to 75 in 2017. This first analysis quantifies sex-differences in the effect of sexual violence on suicide risk. Using adjusted mediation analyses, sexual victimisation was found to explain 49% and 40% of the increased risk women have compared to men in suicidal ideation and suicidal imagery respectively. Last, Hatem et al present preliminary results of a pilot study and the protocol of a future intervention study in the French "Maison des Femmes" (House of women), a center which provides medical, social and judicial support and care for women victim of violence. We discuss pragmatic and ethical concerns, difficulties and importance of such intervention studies. We conclude the session with a discussion with the audience, providing an opportunity for interdisciplinary dialogue and feedback on international experiences. Key messages: Violence against women (VAW) is a widespread phenomenon taking many forms; similar to its effect on women's health. VAW should be accounted for in all large epidemiological studies, using appropriate terms and measurement strategies.